Histoplasma Peritonitis: An Extremely Rare Complication of Peritoneal Dialysis - Asjad Sardar; Bijin Thajudeen; Pradeep V. Kadambi (Case Reports in Nephrology)
Bacterial peritonitis is a common complication of peritoneal dialysis, but fungal peritonitis is unusual and is mostly due to Candida species. Peritonitis due to Histoplasma capsulatum is rare and we report one such case. A 63-year-old female presented with progressively worsening abdominal pain, fever, and altered mental status. She had end-stage renal disease and had been on peritoneal dialysis for 4 years. She had abdominal tenderness without rebound or guarding. Laboratory studies and CT of abdomen were significant for leukocytosis and peritoneal membrane thickening, respectively. Peritoneal dialysis fluid study was consistent with peritonitis and culture of the fluid grew Histoplasma capsulatum. Treatment recommendations include removal of catheter and initiation of antifungal therapy. With the availability of newer antifungals, medical management without removal of PD catheter is possible, but at the same time if there is no response to treatment within a week, PD catheter should be removed promptly.